Agriculture plant leaf Disease detection using Spatial Gray-level Dependence Matrices - Malini, S; Venkadeswari, T; Jeyalakshmi, T Ratha (International Journal of Computer Sciences and Engineering, 2025)
Agriculture is one of the main central divisions of Indian Providence. Indian agriculture segments more than 18 per cent of India’s household product further it helps to provide employment opportunities to 50% of the countries workforce. Fungus, viruses and germs are the main causes that affect the plant leaves. Currently crops face many types of diseases. Damage by the pest is main trait. If good concern is not done in the plants it may lead to grave outcome on vegetation. Discovery of plant illness along with the other routine method in monitoring the plants reduces the drudgery as it ascertains the injection of plants at early stage. Image processing provides better techniques about disease identification. The process has four major processes, initially the color image is transformed to RGB, and then the RGB image is then transferred to HSV for shade generation. After that the green pixels are obtained from the color generation process. The image is analyzed, segmented meaningfully and the texture features are extracted and evaluated from the SGDM matrices.